Real-world experience managing blinatumomab toxicities in adults with relapsed/refractory acute lymphoblastic leukemia. (July 2020) - Crist, MacKenzie; Emadi, Ashkan; Duffy, Alison
Purpose: The purpose of this study was to determine the effect of blinatumomab toxicities on drug therapy modifications in an intended 28-day course of blinatumomab therapy. Methods: Patients with acute lymphoblastic leukemia who received blinatumomab at the University of Maryland Marlene & Stewart Greenebaum Comprehensive Cancer Center from March 1, 2015 to April 30, 2018 were included. The primary objective of this study was to identify the frequency and severity of blinatumomab toxicities that led to drug therapy modifications; secondary objectives were to identify the frequency and duration of modifications and the total dose and duration of therapy received. Results: This study included 23 patients. Seventy-eight percent of patients experienced cytokine release syndrome and/or neurotoxicity. Eighteen drug therapy modifications occurred due to toxicity with a median interruption time of nine hours. Drug therapy was continued for the majority of grade 1 or 2 events and discontinued during grade 3 or 4 neurotoxicity. The median number of days of therapy delivered was 28 days (range, 27–35). A median of 2 h (range, 0–16) of therapy or 0.2% (range, 0–2.4) of a total 28-day cycle was lost due to transition of care. Conclusion: This retrospective study demonstrates a single center experience with blinatumomab toxicity management and appropriate delivery of drug during transitions of care. Overall, these results support to the importance of institutional guidelines in place to facilitate safe and effective delivery of blinatumomab.